Annual migration routes, stopover patterns and diurnal activity of Eurasian Bitterns Botaurus stellaris wintering in China. Issue 1 (2nd January 2019) - Gu, Dehai; Chai, Yisheng; Gu, Yanbing; Hou, Jianhua; Cao, Lei; Fox, Anthony David
ABSTRACT: Capsule: Eurasian Bitterns Botaurus stellaris caught in winter in eastern China summered in the Russian Far East. Aims: To identify migration timing, duration and routes, as well as stopover sites, used by Eurasian Bitterns in the Russian Far East flyway and obtain basic information on behaviour and ecology from tracking data. Methods: We tracked two Eurasian Bitterns caught in China with global positioning system/mobile communications loggers for one and three years respectively, to identify their migration routes and schedules. We used the distance moved between successive fixes to determine their diurnal activity patterns. Results: The two individuals wintered in eastern China and travelled a mean of 4221 ± 603 km (in 2015–17) and 3844 km (2017) to summer in the Russian Far East. Results from one bird have shown that in all three years, the bird was significantly more active during the day than at night, although the absolute differences varied with season, being most nocturnally active in summer. The most surprising result from this bird was the flexibility in spring migration and the lack of summer site fidelity. Conclusion: The study identified previously unknown migration routes of the Eurasian Bittern in East Asia, and suggested that the species is generally more active during the day throughout the year.